The Effect of Transfer Pricing on Financial Distress in the Financial Statements of Mining Companies Listed on the Indonesia Stock Exchange - Muliawati Muliawati; Hilfa Mora Marito Nasution; Erwin Febriansyah; Angelina Nadya Cindy Prasetyo (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the effect of transfer pricing on financial distress and its implications for the quality of financial reports of mining companies listed on the Indonesia Stock Exchange (IDX). The background of this study is based on the importance of financial reports as a source of information for stakeholders, as well as the existence of transfer pricing practices that have the potential to affect the transparency and quality of financial reports, especially in companies experiencing financial distress. This study uses a quantitative approach with a panel data regression analysis method that combines cross-sectional and time series data for the period 2020–2024. The research sample consisted of 10 mining companies selected using a random sampling method. Model testing was carried out using the Chow and Hausman tests, which showed that the best model used was the Fixed Effect Model. The results of the study indicate that transfer pricing and financial distress simultaneously have a significant effect on the quality of financial reports, as evidenced by the F test probability value of 0.000 <0.05. However, partially, the transfer pricing variable does not have a significant effect on financial distress or the quality of financial reports, with a probability value of 0.7482 >0.05. The coefficient of determination (R²) of 0.7367 indicates that the model is able to explain 73.67% of the variation in the dependent variable. Therefore, it can be concluded that although transfer pricing and financial distress jointly influence financial reporting quality, the individual effect of transfer pricing has not yet shown significance. This research is expected to contribute to academics and practitioners in understanding the factors that influence financial reporting quality, particularly in the mining sector.